Mechanisms of young professional engagement in health policy development: a cultural domain approach - Levites Strekalova, Yulia A.; Modjarrad, Lina; Midence, Sara (Frontiers in Public Health, 2024)
Introduction: Engagement in public health policy development is critical to forward-thinking public health policy. There is a robust empirical case to support the prospect of the engagement of young adults in civic and research efforts. However, the literature is limited in conceptualizing the mechanisms of engagement in health policy development from the perspective of young adults. This study applied the concepts and methods of cognitive anthropology to identify the mechanisms of engagement in health policy development from the perspective of young people.Methods: Online elicitation and cognitive domain analysis were applied to collect and analyze the data. Students enrolled in a public health leadership class at a large U.S. southeastern university were invited to participate in an online discussion. Saturation was achieved after the eighth submission. Data were analyzed qualitatively for repetition and recurrence and quantitatively to assess their cultural saliency.Results: Thirty-two students submitted 147 individual engagement ideas. The analysis resulted in 24 unique mechanisms organized into 10 clusters. The most prominent engagement mechanisms included education, peer activities, advocacy, direct involvement, and activism.Discussion: In the dynamic landscape of public health, active involvement in health policy development presents a crucial pathway for leadership among young professionals. The application of cognitive anthropology methods contributes to the emerging science of engagement and allows to identify and measure consensus around the pathways for engagement in health policy development among young professionals.